Juridical Review of Notary Positions Based on the Law on Notary Positions in Welfare Aspects - Adyesha Nur Salma; Taufan Fajar Riyanto; Ira Alia Maerani (Sultan Agung Notary Law Review, 2022)
Notary as a public official who is not paid, either by the state, ministry, or any other party according to UUJN. Sociologically, notaries are stigmatized as one of the respectable professions in society. On the other hand, the presence of a notary in the community has also increased in quantity, so that it is correlated with competition in the task of a notary.This study aims to determine and analyze the responsibilities of a notary in carrying out the position of a notary, to find out and analyze the role of the Indonesian Notary Association in implementing the welfare of a notary in the city of Semarang, and to find out an example of a Sale and Purchase Binding Agreement. The research approach method used in this thesis is an empirical juridical legal research method with descriptive analysis research specifications.Data sources and data collection methods used primary and secondary data which were analyzed qualitatively.The results showed that: First,The position of a notary in Article 1 point 1 UUJN, namely a public official authorized to make authentic deeds and other authorities as referred to in the law. While the term public official is translated from openbare ambtenaren as in Article 1868 of the Civil Code that, "An authentic deed is a deed made in the form determined by law by or before public officials who have power for that, at the place where the deed is. made." On the other hand, Act No. 25 of 2009 concerning Public Services also applies to notaries, because according to Article 15 of the UUJN, the authority of a notary in addition to the UUJN applies, other laws also apply. This means that the Civil Code and the Public Service Law or other laws also apply.Second,Regarding the uncertainty of the minimum honorarium limit from the notary service fee, the Semarang City regional association organization once agreed on a reference regarding the minimum limit for the notary service fee, however, this reference could not last long or was not effectively enforced because after all the economic demands that made notaries compete in getting clients for the sake of to support himself, his family and of course for the operational costs of the office. Meanwhile, as a form of attention from the government, for example, the provision of incentives for the position of a notary has never been proposed to the government.